The Intricacies Involved in the Analysis and Interpretation of Hammer Transfer Stain/s in a Crime Scene - Bandyopadhyay, Samir Kumar; Basu, Nabanita (International Journal of Criminology and Sociology, 2015)
Bloodstain Pattern analysis particularly deals with the reconstruction of dynamic bloodletting events from static bloodstain patterns. Bloodstain patterns often help to sequence events that might have occurred at a crime scene. It can also be used to draw inference about the position of the victim/s, perpetrator/s and bystander/s (if any) at the crime scene. This paper is aimed at intricate analysis/interpretation of transfer stains produced by blunt ended objects at a crime scene. By way of experiments performed within a laboratory setting this paper attempts at establishing that hammer transfer stain or possible weapon transfer stain at a crime scene does not indicate that that particular instrument has been used to murder the victim/s. Also when blood drips over hammer and when a hammer falls under gravity onto a blood pool, the stain patterns formed are particularly different. This particular information under certain circumstances could particularly contribute to sequencing of events at a crime scene. Again, different blunt ended objects were found to produce similar transfer stain patterns. Hence transfer stain patterns should be interpreted in coherence with other relevant circumstantial evidence at the crime scene.